Analisis Pengaruh Pendapatan, Belanja, dan Kemandirian Fiskal terhadap Kinerja Keuangan Daerah: Studi pada Provinsi Sulawesi Selatan - Syaputra, Muh. Yusril Amal; Kamaruddin, Citra Ayni; Regina, Regina; Ma’ruf, Muhammad Imam; Hastuti, Diah Retno Dwi (Jurnal EMT KITA, 2026)
This study analyzes the influence of regional revenue, regional expenditure, and fiscal independence on the financial performance of the South Sulawesi Provincial Government. Fluctuations in revenue, expenditure patterns, and the level of fiscal dependency over the last ten years indicate the dynamics of regional financial management. The study uses a quantitative approach with annual time-series data from 2010–2024. Financial performance is measured through the growth ratio, while the independent variables are derived from the Regional Budget (APBD) financial indicators. The results show that each variable has a different influence on financial performance, mainly through expenditure effectiveness, revenue capacity, and the level of fiscal independence. These findings emphasize the importance of increasing fiscal independence and optimizing productive spending in order to strengthen the sustainability of regional financial management.